2020
DOI: 10.1111/jce.14758
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐based differences in procedural complications associated with atrial fibrillation catheter ablation: A systematic review and meta‐analysis

Abstract: Background: Women undergoing atrial fibrillation catheter ablation (AFCA) have higher rates of vascular complications and major bleeding. However, most studies have been underpowered to detect differences in rarer complications such as stroke/transient ischemic attack (TIA) and procedural mortality. Methods: We performed a systematic review of databases (PubMed, World of Science, and Embase) to identify studies published since 2010 reporting AFCA complications by sex. Six complications of interest were (1) vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
4
13
1
Order By: Relevance
“…The total unadjusted complication rate was higher for females than males (9.58% vs. 7.09%, p = .001); however, it was not significant when adjusted for risks (adjusted OR: 1.23, 95% CI: 0.99–1.53, p = .06). This was despite a lower overall comorbidity burden in females as determined by the Elixhauser comorbidity index, contrary to previous studies 7–9,11 . Other authors had identified that females had higher complications than males attributed to higher comorbidities and later stage presentation 11,15 .…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…The total unadjusted complication rate was higher for females than males (9.58% vs. 7.09%, p = .001); however, it was not significant when adjusted for risks (adjusted OR: 1.23, 95% CI: 0.99–1.53, p = .06). This was despite a lower overall comorbidity burden in females as determined by the Elixhauser comorbidity index, contrary to previous studies 7–9,11 . Other authors had identified that females had higher complications than males attributed to higher comorbidities and later stage presentation 11,15 .…”
Section: Discussioncontrasting
confidence: 65%
“…Most importantly, studies were discrepant in the incidence of in‐hospital death, which was significantly higher in women than in men in some studies, 7,8 while other studies have shown no significant differences 9,10,12–14,19,21 . Complication rates that were higher in females compared to males included pericardial effusion, 7–10 cardiac tamponade, 11,16 major bleeding, 11,13,21 and cerebrovascular events, 7,8 while others have reported no difference in pericardial effusion, 12,14,15,19–21 cardiac tamponade, 12,13,15,19 major bleeding, 17 and cerebrovascular events 10,12,13,15,19 . It is unclear whether these complication rates contribute to overall in‐hospital death rates, length of stay, and costs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observations suggest that specific studies investigating more aggressive preventive measures in diabetic women are warranted. Of note, a higher rate of complications has been reported in women with catheter ablation of AF, which may be partially attributable to older age and a higher prevalence of comorbidities (including diabetes) at the time of ablation [38].…”
Section: Table 2 Unadjusted and Multivariable-adjusted Hrs For Incidence Of Af Comparing People With And Without Diabetes By Sex And Hazamentioning
confidence: 99%